2020
DOI: 10.3390/s20247116
|View full text |Cite
|
Sign up to set email alerts
|

Applying Convolutional Neural Networks to Predict the ICD-9 Codes of Medical Records

Abstract: The International Statistical Classification of Disease and Related Health Problems (ICD) is an international standard system for categorizing and reporting diseases, injuries, disorders, and health conditions. Most previously-proposed disease predicting systems need clinical information collected by the medical staff from the patients in hospitals. In this paper, we propose a deep learning algorithm to classify disease types and identify diagnostic codes by using only the subjective component of progress note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…Infection and Drug Resistance 2021:14 1950 temperature, 28 and ICD-9 codes of medical records, 51 and these studies suggested that the LSTM and CNN also showed high accuracy for forecasting the target series. Therefore, further work is supposed to compare the forecasting ability between our proposed combined method and the above deep mining methods.…”
Section: Dovepressmentioning
confidence: 94%
“…Infection and Drug Resistance 2021:14 1950 temperature, 28 and ICD-9 codes of medical records, 51 and these studies suggested that the LSTM and CNN also showed high accuracy for forecasting the target series. Therefore, further work is supposed to compare the forecasting ability between our proposed combined method and the above deep mining methods.…”
Section: Dovepressmentioning
confidence: 94%
“…In our previous study [13], we employed a CNN based network to predict ICD-9 code, which scores the recall of 58% in chapter level. In this work, we applied the LSTM and GRU network to predict ICD codes.…”
Section: Related Workmentioning
confidence: 99%
“…Many countries consider ICD as the tool to follow up death and statistics of death. The ICD system has more than one version, which depends on the situation in different countries and their clinical conditions [13]. Various countries have adopted the ICD-10, including the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…for a single admission. More and more attention has been paid to EMR-based auxiliary diagnosis and treatment, such as clinical knowledge question answering [1,2], health risk warning [3][4][5][6], auxiliary diagnostic [7,8] and electronic prescription recommendation [9,10]. Medication recommendation is an important research direction in EMRbased applications.…”
Section: Introductionmentioning
confidence: 99%